2019
DOI: 10.1108/jarhe-02-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Iranian doctoral students’ perceptions of publication in English

Abstract: Purpose The purpose of this paper is to investigate the English for publication purpose practices of doctoral students in Iran. The overall objective was to explore their motives, hurdles and strategies in academic writing. Design/methodology/approach This case study draws on a narrative inquiry to explore nine science and engineering doctoral students’ perceptions of academic publication. The data were analyzed through a hybrid process of inductive and deductive thematic analysis. Findings The qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Some studies have previously been conducted to examine the graduate students' challenges of writing for academic publication, particularly in doctoral education context. Grounded in narrative inquiry, Rezaei & Seyri (2019) investigated nine Doctor of Science and Engineering students' scholarly publication experiences. One of the essential findings of their study is the participants' challenges in their publication process.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have previously been conducted to examine the graduate students' challenges of writing for academic publication, particularly in doctoral education context. Grounded in narrative inquiry, Rezaei & Seyri (2019) investigated nine Doctor of Science and Engineering students' scholarly publication experiences. One of the essential findings of their study is the participants' challenges in their publication process.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to writing a journal article and its publication process, it was revealed that the process itself came out for various motivations and reasons from the writer. In line with this, Rezaei & Seyri [7] proven that the writer intends to write a journal article for some reasons such as for academic requirements, for better self-resume and sharing knowledge to the world. In terms of academic requirements, it is well-known for most educational institutions which regulate their students to write and publish some articles before they finish their study in those institutions.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Furthermore, publishing journals also means for an evaluation system and for sharing. In line with this, Rezaei & Seyri [7] revealed that for professor and similar professional purposes, the ranking system is evaluated based on the amount of journal publications. Submitting international journals can increase their chance to get promotions [8].…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations